Prophylaxis of functional violations of spine by liquidation of post-loadings changes in locomotorium of overhead acrobats - Maximova Y.A (Kharkov National Pedagogical University, 2012)
The attempt of liquidation of convertible changes of locomotorium is undertaken, as a result of pathobiomechanical influence of intensive, specific training activity of acrobats. In an experiment took part 40 sportsmen aged 12-13 years. It is set that 75% sportsmen in the process of training and after its completion extremely rarely utillize facilities and methods of renewal. Grounded and developed program, directed on liquidation of post-loadings changes in the system of spine of overhead acrobats, gettings busy on the stage of the specialized base preparation. Development of complex of exercises principle of minimum physiological training sufficientness (minimum optimum) of physical exercises was underlaid. It is shown that the biomechanics correction of the functional state of spine, reduction of post-loadings deformations, improvement of metabolism of the trophic systems of intervertebral disks, for certain reduced pathogenic influence of the intensive specific loadings on the spine of sportsmen.